Reality of Minor Marriage Dispensation Arrangements in Indonesia and Bangladesh - Ramadhani, Dwi Aryanti; Sakti, Muthia; Febriana, Meutia Caesar (UNISKA LAW REVIEW, 2023)
Law Number 16 of 2019, concerning Amendments to Law Number 1 of 1974 concerning Marriage, has substantially renewed the age of Marriage to 19 years for boys and girls as a form of government effort to reduce the number of child marriages. However, Article 7 Paragraph (2) provides opportunities for child marriages under the age of 19 years. The Court gives this opportunity through the provision of marriage dispensation. Marriage dispensation is also found in Bangladeshi marriage law. Article 19 of Bangladesh's Child Marriage Restriction Act states that girls under 18 and boys under 21 can enter into Marriage if parental or court approval can be obtained in exceptional circumstances. The prevailing marriage dispensation breaks the expectation of a decline in child marriages. This study aims to explain the provision of dispensation for Marriage to minors, which compares the arrangements in Indonesia and Bangladesh. This research is qualitative research with a normative juridical approach. Solve problems using a statutory approach and a comparative approach with data obtained through a literature study, which is described in an analytical descriptive manner. The results of the study show that there is a difference in regulating the dispensation of Marriage for minors in Indonesia and Bangladesh. The conclusion of this study shows that regulations in both countries granting dispensation for Marriage to minors are contradictory to changes in the rules for the age limit for Marriage.